Analisis Perbandingan Persepsi Antropomorfik Agen Bot antara Generasi Y dan Generasi Z - Primanto, Alfian Budi; Amin, Muh. Sirojuddin (Jurnal Ekonomi Modernisasi, 2024)
This study investigates the significant differences between Generation Y and Generation Z in evaluating the perceived humanness or anthropomorphism of a designed chatbot and the effect of that evaluation on their intention to reuse it. Utilizing a scenario-based experiment and a survey, we examined the responses of 328 participants aged 17-39 years. Our analysis, employing independent sample t-tests and regression, revealed that Generation Y consistently rates the chatbot higher in virtual appearance, cognitive empathy, emotional empathy, moral virtue, and sociality compared to Generation Z. Additionally, cognitive empathy appears less influential in shaping reuse intentions as our designed bot failed to understand users' complex queries regarding promotional information and credit availability and calculations. The study also highlights the limitations of relying solely on static PDF-based knowledge, which restricts the chatbot's flexibility and depth in handling diverse queries.